Efektivitas Pemberian Telur Rebus Ayam Ras Terhadap Percepatan Peyembuhan Luka Perineum - Azis, Marlina Azis; Triananinsi, Nurhidayat; Alza, Nurfaizah (POLTEKKES KEMENKES MANADO, 2022)
Background : Perineal injuries are tears in the birth canal caused by the position when pressing on the mother, large baby, primigravida mother, usually caused by factors the midwife did not support properly during delivery. The healing of stitches on the perineum is influenced by perineal wound care, nutritional factors, quality of sleep and wound care and early mobilization. Objective : to find out